THE PROBLEM OF "ZERO ELEMENTS" IN THE WORKS OF D. I. MENDELEEV. NEUTRON MATTER AS A PRIMARY COSMOLOGICAL AND MODERN DARK MATTER OF THE UNIVERSE - Ryazantsev, G. B.; Lavrenchenko, G. K.; Nedovesov, S. S. (Одеські астрономічні публікації, 2019)
D.I. Mendeleev assumed the existence of elements X ("Newtonium") and Y ("Coronium") in front of hydrogen in the zero group of the periodic system of chemical elements (PS). It should be recalled that Mendeleev was not mistaken in his predictions of new elements. When he applied the periodic law (PL) to analogues of boron, aluminum and silicon, he had complete confidence in success, because everything was obvious to him there. The idea of elements before hydrogen came to him immediately after the opening of the PL, but he published this only before his death. This question haunted him almost his entire creative life. D.I.Mendeleev did not have time to solve this problem, and his students and followers tried to forget it as “erroneous”. It should be noted that after D.I.Mendeleev the question of “zero” elements was repeatedly raised by many authors both in the past and in the present centuries, however, for brevity, we only mention the very first and most famous of them: for example, Ernest Rutherford in 1920 and Andreas von Anthropoff in 1926. Anthropoff was the first to propose the term "neutronium" to refer to a hypothetical element with atomic number zero, which he placed at the beginning of the periodic table (PT). At present, neutron matter, like neutron stars, is a recognized reality in astro- and nuclear physics. From the standpoint of general chemistry, a neutron substance can be classified as chemically simple (that is, it cannot be decomposed into simpler ones by chemical means), then the question inevitably arises of the corresponding element and its place in the PS. Based on the logic of the PL – (ordinal number – electric charge) – the ordinal number of neutron matter will correspond to zero, which makes us remember and develop the ideas of Dmitry Ivanovich Mendeleev about the zero group and period. Based on the works of Tamm, Hund and Migdal, the possibility of the stable existence of neutron matter at the micro level, and not only at the macro level, as is now believed in astrophysics, is stated. Neutron matter is considered as the primary cosmological substance, a candidate for dark matter and its production in laboratory conditions on Earth.